Analisis Tingkat Kepuasan Pelanggan dan Loyalitas Pelanggan terhadap Cafe Infinity Coffee - Muhammad Nuruddin Prathama; Muhammad Nur Aidi; Agus Mohamad Soleh (Department of Statistics, IPB, 2022)
Cafe and restaurant businesses are some of the most competitive businesses and have a sizeable market in Jakarta. In this case, the restaurant owner must know the wishes and preferences of the buyer. This research was conducted in one of the cafes in Jakarta